Hybrid fuzzy adaptive control strategies on double acting pneumatic cylinder rod-piston positioning - Mohd Iskandar Putra, Azahar (2020)
The pneumatic system is widely used in the industry due to its advantages such as high weight to power ratio, high travel speed, clean fluid medium and cost-effectiveness. However, it is quite challenging to control the position of the pneumatic rod-piston due to the high nonlinearity behavior and friction as well as uncertainties in the parameters of the pneumatic systems. In terms of the control system, there are two approaches which are model-free and model-based control. For the model-free control, it is difficult to obtain adequate position accuracy performance by using the conventional Proportional, Integral and Derivative (PID) for the highly nonlinear system, while, for the model-based control, the conventional Sliding Mode Controller (SMC) suffers from chattering phenomenon creating the state trajectory oscillations around the sliding surface. Therefore, this study has taken the initiative to propose a robust control system strategy using the Fuzzy Self-Adaptive (FSA) element to tackle the aforementioned issues using a pneumatic proportional valve with double-acting cylinder (PPVDC) system model as a platform to achieve the positioning precision. For the model-free control approach, an improvement has been done on the PID control system by integrating the FSA and applying the cascade method, forming the Cascade FSAPID (CFSAPID). Meanwhile, for the model-based control approach, the Dual-Stage FSAISMC (DFSAISMC) is developed by integrating two FSA methods. Furthermore, the DFSAISMC can be improved further by integrating the hybrid switching between the DFSAISMC and Force FSAISMC (FFSAISMC), forming the HPF-FSAISMC. For the model-free control approach, overall simulation results showed that the CFSAPID controller is able to minimize the overshoot at 3.67 mm and provide the fastest response of settling time at 1.4 s at 10 kg external load condition. Moreover, compared to PID, CPID and FSAPID, the oscillation in both pressure chambers is improved at 90% lower by using CFSAPID. Meanwhile, for the model-based control approach, both DFSAISMC and HPF-FSAISMC are applied to the PPVDC model plant. Simulation results showed that the DFSAISMC controller was able to reduce the overshoot and settling time, at 90% and 1.25 s, respectively, compared to ISMC and FSAISMC controllers. On the other hand, simulation results of the PPVDC model plant with HPF-FSAISMC showed that the proposed controller is capable of eliminating the oscillation on the rod-piston displacement, while also performing 0.5 s faster in settling time compared to DFSAISMC controller and far better compared to ISMC and FSAISMC controllers. The comparison study is finalized with the comparison of both CFSAPID and HPF-FSAISMC controllers as the best model-free and model-based control designed, respectively, for the PPVDC system. The simulation was done using the step trajectory with 15-20 kg external load and 100N force disturbance at the time period of 3 s. HPF-FSAISMC controller showed better robustness compared to the CFSAPID controller in terms of fast response at 1.21 s settling time with almost zero overshoot. Moreover, the HPF-FSAISMC controller performs disturbance rejection where the pressure levels were sustained at 4.2 Pa and 3 Pa for both pressure chambers, respectively. The overall results conclude that the proposed HPF-FSAISMC controller is able to stabilize the internal pressure and internal frictions of the pneumatic cylinder chambers, which are the main parameters for the pneumatic air compression, resulting in almost zero steady-state-error.